CHILDREN VOCABULARY MASTERY OF ENGLISH AS A FOREIGN LANGUAGE FROM YOUTUBE VIDEO - Dede Irawan (Jurnal Scientia, 2022)
This research focuses on children's vocabulary mastery of English as a Foreign Language from YouTube Video, whereas the writer uses the qualitative descriptive method to investigate the way mastery of vocabulary in the children, it will analyze the form of vocabulary is mastered, the participant in this research is the 6- and 7-years old child. The data collecting technique used questionnaires and interview to explore the type of vocabulary and the vocabulary mastered by children in this research, the writer chose 6 years old and 7 years old children as a participant. The result of this research shows the type of English vocabulary produced by children is included vocabulary receptive to English vocabulary where a 6-year-old can master 1 verb, 6 Nouns, and 1 Phrase, the child can mention some vocabulary and the child can know the meaning of vocabularies, but the child finds difficulties to write the vocabularies on the paper, Whereas the 7-year-old can produce 6 verbs, 6 nouns, 2 phrases and 4 sentences from the YouTube Channel, the child can mention and understand the meaning of vocabularies, besides that the child can write the vocabularies fluently.